2011
DOI: 10.1002/er.1852
|View full text |Cite
|
Sign up to set email alerts
|

Performance assessment of heat pumps using HFC125/HCs mixtures

Abstract: SUMMARY The analysis of heat pump cycles with and without an internal heat exchanger (IHE) is carried out in the paper, in which HFC125/HCs binary mixtures are used as the alternative refrigerants. And the cycle performance under different operation conditions is also compared. The results show that when the mass fraction of HFC125 ranges from 10 to 20%, the coefficient of performance (COP) for HFC125/HC290 (M1) mixtures is 0.92 and 1.01% lower than that of HCFC22 and HFC134a, respectively. For HFC125/HC600 (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…There are few studies on the flow heat transfer characteristics of the two-stage spiral casing heat exchanger connected by straight pipe sections. The effect of structural parameters on the flow heat transfer performance of heat exchangers, the effect of structural parameters and inner and outer tube flow rates on the overall heat transfer coefficients, ε-NTU, pump work and pressure drop, combined thermohydraulic performance factors and inner and outer tube Nusselt number were previously discussed by this group [14] , and the preliminary experimental studies showed that this structure heat exchanger has better heat transfer efficiency [15,16] . This study aims to further reveal the influence of flow parameters on the heat transfer performance of a two-stage spiral casing heat exchanger, and the results will provide theoretical guidance for efficient heat exchanger operation in heat pump systems.…”
Section: Introductionmentioning
confidence: 88%
“…There are few studies on the flow heat transfer characteristics of the two-stage spiral casing heat exchanger connected by straight pipe sections. The effect of structural parameters on the flow heat transfer performance of heat exchangers, the effect of structural parameters and inner and outer tube flow rates on the overall heat transfer coefficients, ε-NTU, pump work and pressure drop, combined thermohydraulic performance factors and inner and outer tube Nusselt number were previously discussed by this group [14] , and the preliminary experimental studies showed that this structure heat exchanger has better heat transfer efficiency [15,16] . This study aims to further reveal the influence of flow parameters on the heat transfer performance of a two-stage spiral casing heat exchanger, and the results will provide theoretical guidance for efficient heat exchanger operation in heat pump systems.…”
Section: Introductionmentioning
confidence: 88%
“…66 Therefore, in order to compare the performance of various refrigerant blends, average (mean) evaporating (t e,m ) and condensing temperatures (t k,m ) are defined and they are expressed as follows. 6668
Figure 3.P-h chart for zeotropic refrigerants.
…”
Section: Methodsmentioning
confidence: 99%
“…Referring to Figure 4, various process and losses that take place in actual VCR cycle are stated as follows: 6370 Superheating of vapour refrigerant in the evaporator (1j-1i), heat gain across suction line (1i-1 h), pressure drop in the suction line (1 h-1 g), pressure loss in the suction valve (1 g-1), actual compression work (1-2), pressure loss in the discharge valve (2-2 g), pressure drop in the delivery line (2 g-2 h), desuperheating and heat loss of refrigerant in the delivery line (2 h-2i), pressure drop across condenser (2 h-3), subcooling of liquid refrigerant through condenser (3-3 g), heat gain of refrigerant in liquid line (3 g-3 h), expansion process (3 h-4) and pressure drop across evaporator (4-1j), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zeotropic refrigerants will evaporate and condense through a range of temperatures due to its temperature glide and also temperature glide causes the change in composition during evaporation and condensation phase change processes as shown in Figure 4. Therefore, in order to compare the performance of various refrigerant mixtures, average (mean) evaporating (t e,m ) and condensing temperature (t k,m ) are defined and they are as follows 46–48 where te,m is the mean evaporating temperature (℃), te is the dew point temperature at the evaporation process (℃), te1 is temperature at entry of the evaporation process (℃), tk,m is the mean condensing temperature (℃), tk' is the bubble point temperature at the condensation process (℃), and tk is the dew point temperature at the condensation process (℃). Pressure–enthalpy (P-h) chart for zeotropic refrigerants is different from pure and azeotropic refrigerants and it is shown in Figure 4.…”
Section: Methodsmentioning
confidence: 99%